ODS alloy with dispersively distributed nano oxide and preparation method of ODS alloy

By preparing core-shell structured rare earth oxide nanoparticles and combining them with liquid-phase mixing and additive manufacturing, the problem of easy agglomeration of nanoparticles in ODS alloys was solved, thereby improving the mechanical properties and production efficiency of the material.

CN121156263APending Publication Date: 2025-12-19GUIZHOU UNIV
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202511341900.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-19
Publication Date
2025-12-19

AI Technical Summary

Technical Problem

In existing ODS alloy production methods, nanoparticles are prone to agglomeration, leading to a decline in material properties. Furthermore, traditional methods suffer from problems such as long process flow, high cost, and poor batch stability.

Method used

By preparing core-shell structured rare earth oxide nanoparticles, and using liquid-phase mixing and additive manufacturing techniques, the dispersion and distribution of nanoparticles are controlled to avoid agglomeration and improve wettability and chemical stability.

Benefits of technology

Uniform dispersion of nanoparticles was achieved, reducing energy consumption and dispersion time, maintaining the sphericity and flowability of metal powder, and improving the mechanical properties of ODS alloys.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121156263A_ABST
    Figure CN121156263A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of additive manufacturing, and discloses an ODS alloy with dispersively distributed nano oxide and a preparation method of the ODS alloy, and the prepared rare earth nano oxide with a core-shell structure and coated with a metal simple substance improves the wettability of the nano oxide in molten metal, so that the wettability of the nano oxide in molten metal is improved. And meanwhile, rare earth oxide can be prevented from reacting with elements in steel to change chemical components. The size of nano particles in the prepared ODS alloy can be controlled to be 20 nm or below, the nano particles are distributed in a dispersed mode, the number of the nano particles is large, and performance improvement of the ODS alloy is facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application belongs to the technical field of additive manufacturing, and relates to an ODS alloy with dispersedly distributed nanometer oxides and a preparation method thereof. BACKGROUND

[0002] Additive manufacturing technology is a process of accumulating materials layer by layer to manufacture a solid object based on a digital model. This method can directly manufacture finished parts with complex structures from customized powder materials, significantly shortening the production route. ODS (oxide dispersion strengthened) alloys have nanometer oxides dispersed in the alloy matrix, and still have good mechanical properties under high radiation intensity and high temperature conditions. ODS alloys can be applied to high-temperature gas turbines, engine turbine pipes and nuclear reactor cladding and other extreme service environments. The strengthening phase in the ODS alloy is nanometer oxide, and the size, distribution and volume fraction of the nanometer oxide directly affect the service performance. However, as particles in the transition zone between atomic clusters and macroscopic objects, nanometer particles have volume effect, surface effect, quantum size effect and macroscopic quantum tunneling effect, and have completely different characteristics compared with macroscopic substances. Nanometer particles have a large surface energy and are easy to agglomerate to form large-size particles, thereby greatly reducing the use performance of the material. Therefore, mastering the control method of nanometer particle dispersion has been one of the important topics of ODS alloy research.

[0003] At present, the production of ODS alloys mainly adopts powder metallurgy and liquid metal methods. In these methods, nanometer particles are introduced in the form of added rare earth oxide monomer. However, there are many disadvantages, such as: in the powder metallurgy method, although nanometer-sized strengthening phases can be stably obtained due to the absence of a molten pool, there are some common problems, such as long process flow, small single batch, poor batch stability, high manufacturing cost and the like; the liquid metal method has low cost and is suitable for large-scale production, but nanometer particles in the molten metal will collide due to buoyancy, van der Waals force and capillary force, causing the size of the nanometer particles to change; nanometer particles are often directly mixed with metal powder through mechanical alloying, which not only needs a long time for sufficient mixing and high energy consumption, but also is easy to react with active elements such as aluminum and titanium in the alloy matrix, causing the chemical composition of the nanometer oxide to change.

[0004] Although it is currently believed that improving the addition method of nanometer particles can reduce the agglomeration of nanometer particles, there is little research on maintaining the morphology and chemical composition of nanometer particles by regulating the structure of nanometer particles. In view of the above research status, the application proposes a rare earth oxide nanoparticle with a core-shell structure, optimizes the addition method thereof, and obtains an ODS alloy with dispersedly distributed nanometer oxides through additive manufacturing. SUMMARY

[0005] To achieve the purpose of the application of additive manufacturing ODS alloy by regulating the structure of nanometer rare earth oxide, the application adopts the following technical scheme: A preparation method of ODS alloy with dispersedly distributed nanometer oxides, comprising the following steps: S1, nanometer rare earth oxide and dispersant are added into liquid for sufficient dispersion to prepare a mixture with fully dispersed nanometer particles; S2, soluble metal salt is added into the mixture to dissolve the metal salt, and pH regulator is added under stirring to adjust the pH, so that the metal salt is fully hydrolyzed and precipitated to coat the surface of the nanometer rare earth oxide; S3, the precipitate is extracted for washing and drying, and the dried powder is calcined in air atmosphere and then reduced in reducing atmosphere to obtain nanometer rare earth oxide particles coated with metal elements; S4, the nanometer rare earth oxide particles coated with metal elements are mechanically stirred and ultrasonically dispersed with metal powder for additive manufacturing in liquid until there is no obvious color separation and stratification, and then the mixture is dried to obtain a mixed powder, the mixed powder is used for additive manufacturing to obtain ODS alloy with dispersedly distributed nanometer oxides.

[0006] As a preferred scheme of the preparation method of ODS alloy with dispersedly distributed nanometer oxides, in the step S1, the rare earth oxide is at least one of cerium oxide, yttrium oxide, lanthanum oxide and samarium oxide.

[0007] As a preferred scheme of the preparation method of ODS alloy with dispersedly distributed nanometer oxides, in the step S1, the dispersant is polyvinylpyrrolidone or sodium dodecyl sulfate; the liquid is ultrapure water, deionized water or ethanol solution; and the mixture is colloid or suspension.

[0008] As a preferred scheme of the preparation method of ODS alloy with dispersedly distributed nanometer oxides, in the step S2, the metal salt is iron nitrate, ethyl alcohol iron, chromium nitrate, ammonium metatungstate and ammonium paratungstate.

[0009] As a preferred scheme of the preparation method of ODS alloy with dispersedly distributed nanometer oxides, in the step S2, the pH regulator is ammonia water or sodium hydroxide, and the adjusted pH is 8-12.

[0010] As a preferred scheme of the preparation method of ODS alloy with dispersedly distributed nanometer oxides, in the step S2, the mass ratio of the metal introduced by the metal salt to the nanometer rare earth oxide is (1-10):1.

[0011] As a preferred scheme of the preparation method of the ODS alloy with the dispersedly distributed nano-oxides according to the present application, in step S3, the anhydrous ethanol and distilled water are used for washing, the drying temperature is 60-90℃, and the drying time is 6-12h.

[0012] As a preferred scheme of the preparation method of the ODS alloy with the dispersedly distributed nano-oxides according to the present application, in step S3, the calcination temperature is 400-600℃, and the calcination time is 0.5-2h.

[0013] As a preferred scheme of the preparation method of the ODS alloy with the dispersedly distributed nano-oxides according to the present application, in step S3, the reducing atmosphere is hydrogen, the reducing temperature is 600-900℃, and the reducing time is 1-3h.

[0014] As a preferred scheme of the preparation method of the ODS alloy with the dispersedly distributed nano-oxides according to the present application, in step S4, the liquid is deionized water or an ethanol solution.

[0015] As a preferred scheme of the preparation method of the ODS alloy with the dispersedly distributed nano-oxides according to the present application, in step S4, the mechanical stirring time is 2-4h, and the ultrasonic power is 100-400W.

[0016] An ODS alloy with dispersedly distributed nano-oxides is prepared by the above preparation method of the ODS alloy with dispersedly distributed nano-oxides.

[0017] As a preferred scheme of the ODS alloy with dispersedly distributed nano-oxides according to the present application, the dispersedly distributed nano-rare earth oxides are the nano-rare earth oxides coated with elemental metals with a core-shell structure, and the size is below 20nm.

[0018] The present application has the following advantages: (1) Compared with the current direct addition of rare earth oxide nanoparticles, the present application prepares a nano-rare earth oxide coated with elemental metals with a core-shell structure, improves the wettability of the nano-rare earth oxide in the molten metal, and avoids the change of the chemical composition of the nano-rare earth oxide due to the reaction with the oxides in the steel.

[0019] (2) Compared with the traditional mechanical alloying, the present application uses the liquid mixing method to uniformly mix the nano-rare earth oxide particles coated with elemental metals and the metal powder for additive manufacturing, reduces the dispersion time and energy consumption, and also retains the original sphericity and fluidity of the metal powder.

[0020] (3) The ODS alloy prepared by the application has nano-particles with a size controlled below 20nm, a dispersed distribution and a large quantity, which is beneficial to the performance improvement of the ODS alloy. BRIEF DESCRIPTION OF DRAWINGS

[0021] In order to more clearly illustrate the technical solutions in the embodiments of the present application or the prior art, the following will briefly introduce the drawings needed to be used in the embodiments or the prior art description. Obviously, the drawings in the following description only show some embodiments of the present application, and other drawings can be obtained by those skilled in the art without any creative effort on the basis of the drawings shown.

[0022] Figure 1 The morphology of the mixed powder obtained after drying in step S4 in the embodiment 1 of the present application.

[0023] Figure 2 The morphology of the rare earth oxide strengthening phase in the ODS steel prepared in the embodiment 1 of the present application.

[0024] The implementation, functional features and advantages of the present application will be further described with reference to the embodiments and the drawings. DETAILED DESCRIPTION

[0025] The technical solutions in the embodiments will be described clearly and completely below. Obviously, the described embodiments are only some of the embodiments of the present application, but not all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without any creative effort belong to the protection scope of the present application.

[0026] The main purpose of the present application is to provide an ODS alloy with dispersedly distributed nano-oxides and a preparation method thereof.

[0027] According to one aspect of the present application, the present application provides the following technical solutions: A preparation method of an ODS alloy with dispersedly distributed nano-oxides, comprising the following steps: S1, adding nano-rare earth oxides and a dispersing agent into a liquid, and using mechanical stirring or ultrasonic treatment to fully disperse, to obtain a mixture with fully dispersed nano-particles; S2, adding soluble metal salts into the mixture to dissolve the metal salts, and adding a pH regulator to adjust the pH under stirring, so that the metal salts are fully hydrolyzed and precipitated to coat the surface of the nano-rare earth oxides; S3, extracting the precipitate for washing and drying, and calcining the dried powder in an air atmosphere, and then reducing in a reducing atmosphere, to obtain nano-rare earth oxide particles coated with metal elements; S4, mechanically stirring and ultrasonic dispersing the metal element coated nanometer rare earth oxide particles and the metal powder for additive manufacturing in a liquid until there is no obvious color stratification, and then drying to obtain a mixed powder, using the mixed powder for additive manufacturing to obtain an ODS alloy with dispersed nanometer oxides.

[0028] Compared with the current direct addition of rare earth oxide nanoparticles, the present application prepares a nanometer rare earth oxide coated with a metal element with a core-shell structure, improves the wettability of the nanometer rare earth oxide in the molten metal, and can also avoid the reaction of the nanometer rare earth oxide with the oxides in the steel to change its chemical composition. Compared with traditional mechanical alloying, the present application mixes the nanoparticles dispersed in the liquid phase with the metal powder, reduces the dispersion time and energy consumption, and also retains the original sphericity and fluidity of the metal powder.

[0029] Preferably, in the step S1, the rare earth oxide is at least one of cerium oxide, yttrium oxide, lanthanum oxide, and samarium oxide; the dispersant is polyvinylpyrrolidone or sodium dodecyl sulfate; the liquid is ultrapure water, deionized water, or anhydrous ethanol; and the mixture is a colloid or a suspension.

[0030] Preferably, in the step S2, the metal salt is iron nitrate, iron ethanoate, chromium nitrate, ammonium metatungstate, or ammonium paratungstate; the pH adjuster is ammonia water or sodium hydroxide, and the pH is adjusted to 8-12; and the mass ratio of the metal introduced by the metal salt to the nanometer rare earth oxide is (1-10):1. Specifically, the pH can be, for example, any one of 8, 9, 10, 11, and 12, or a range between any two of them; and the mass ratio of the metal introduced by the metal salt to the nanometer rare earth oxide can be, for example, any one of 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, and 10:1, or a range between any two of them.

[0031] Preferably, in the step S3, the washing is performed using anhydrous ethanol and distilled water, the drying temperature is 60-90℃, the drying time is 6-12h; the calcination temperature is 400-600℃, the calcination time is 0.5-2h; the reducing atmosphere is hydrogen, the reducing temperature is 600-900℃, and the reducing time is 1-3h. Specifically, the drying temperature can be, for example, any one of 60℃, 65℃, 70℃, 75℃, 80℃, 85℃, 90℃, or a range between any two of them; the drying time can be, for example, any one of 6h, 7h, 8h, 9h, 10h, 11h, 12h, or a range between any two of them; the calcination temperature can be, for example, any one of 400℃, 450℃, 500℃, 550℃, 600℃, or a range between any two of them; the calcination time can be, for example, any one of 0.5h, 1h, 1.5h, 2h, or a range between any two of them; the reducing temperature can be, for example, any one of 600℃, 650℃, 700℃, 750℃, 800℃, 850℃, 900℃, or a range between any two of them; and the reducing time can be, for example, any one of 1h, 1.5h, 2h, 2.5h, 3h, or a range between any two of them.

[0032] Preferably, in the step S4, the liquid is deionized water or an ethanol solution; the mechanical stirring time is 2-4h, and the ultrasonic power is 100-400W. The amount of the metal element-coated nanometer rare earth oxide particles and the additive manufacturing metal powder can be adjusted according to the composition of the alloy to be prepared. Specifically, the mechanical stirring time can be, for example, any one of 2h, 2.5h, 3h, 3.5h, 4h, or a range between any two of them, and the ultrasonic power can be, for example, any one of 100W, 150W, 200W, 250W, 300W, 350W, 400W, or a range between any two of them.

[0033] According to another aspect of the present application, the present application provides the following technical solutions: An ODS alloy with dispersedly distributed nanometer oxides is prepared by the above-mentioned method for preparing an ODS alloy with dispersedly distributed nanometer oxides, wherein the dispersedly distributed nanometer rare earth oxides are nanometer rare earth oxides with a core-shell structure coated with a metal element, and the size of the nanometer rare earth oxides is below 20nm.

[0034] Preferably, the ODS alloy with dispersedly distributed nanometer oxides is an ODS FeCrAl stainless steel with dispersedly distributed nanometer oxides, and the tensile strength thereof is ≥750MPa.

[0035] The technical solutions of the present application are further described below in combination with specific embodiments.

[0036] Embodiment 1 A method for preparing an ODS FeCrAl stainless steel with dispersed nanometer oxides, comprising the following steps: S1, 2g of 50nm Y2O3 and 1g of polyvinylpyrrolidone were added to 200mL of ethanol solution, and ultrasonic + mechanical stirring was used to ensure that the nanoparticles were fully dispersed; S2, 2.7g of ammonium metatungstate was added to the solution, after fully dissolving, sodium hydroxide was added while stirring, the pH was adjusted to 12, and the precipitate was obtained by centrifugal separation; S3, the above product was repeatedly washed with anhydrous ethanol and distilled water, then placed in an 85°C oven for drying for 24h, then placed in a tube furnace and calcined at 500°C in air atmosphere for 2h to remove impurities, then in a hydrogen atmosphere at 600°C for 3h, to obtain yttrium oxide nanoparticles coated with elemental tungsten; S4, the prepared nanoparticles were fully dispersed in anhydrous ethanol with 2kg of Fe-Cr-Al stainless steel powder for additive manufacturing, mechanical stirring + ultrasonic dispersion was carried out until there was no obvious color stratification, the mechanical stirring time was 2h, the ultrasonic power was 100W, then drying was carried out to obtain a mixed powder morphology as shown in Figure 1 , the metal powder for additive manufacturing maintains good sphericity, and the surface is uniformly dispersed with the prepared nanometer oxides.

[0037] S5, the mixed powder was used for additive manufacturing to obtain an ODS FeCrAl stainless steel with dispersed nanometer oxides, the tensile strength was 773MPa, and the morphology of the rare earth oxide strengthening phase was as shown in Figure 2 , it can be seen that the oxides are uniformly dispersed and the average size is 18.3nm.

[0038] Example 2 A method for preparing an ODS FeCrAl stainless steel with dispersed nanometer oxides, comprising the following steps: S1, 2g of 50nm Y2O3 and 1g of polyvinylpyrrolidone were added to 200mL of ethanol solution, and ultrasonic + mechanical stirring was used to ensure that the nanoparticles were fully dispersed; S2, 2.7g of ammonium metatungstate was added to the solution, after fully dissolving, sodium hydroxide was added while stirring, the pH was adjusted to 12, and the precipitate was obtained by centrifugal separation; S3, the above product was repeatedly washed with anhydrous ethanol and distilled water, then placed in an 85°C oven for drying for 24h, then placed in a tube furnace and calcined at 500°C in air atmosphere for 2h to remove impurities, then in a hydrogen atmosphere at 600°C for 3h, to obtain yttrium oxide nanoparticles coated with elemental tungsten; S4, the prepared nanoparticles are dispersed in 2 kg of Fe-Cr-Al stainless steel powder for additive manufacturing in anhydrous ethanol, mechanical stirring + ultrasonic dispersion is carried out until there is no obvious color stratification, the mechanical stirring time is 2 h, the ultrasonic power is 100 W, then drying is carried out to obtain a mixed powder, the metal powder for additive manufacturing maintains good sphericity, and the prepared nano-oxides are uniformly dispersed on the surface.

[0039] S5, the mixed powder is used for additive manufacturing to obtain an ODS FeCrAl stainless steel with dispersed nano-oxides, the tensile strength is 767 MPa, the oxide distribution is dispersed and uniform, and the average size is 19.8 nm.

[0040] Example 3 A preparation method of an ODS FeCrAl stainless steel with dispersed nano-oxides, comprising the following steps: S1, 2 g of 50 nm Y2O3 and 1 g of polyvinylpyrrolidone are added to 200 mL of an ethanol solution, and ultrasonic + mechanical stirring is used to ensure that the nanoparticles are fully dispersed; S2, 27.2 g of ammonium metatungstate is added to the solution, after being fully dissolved, sodium hydroxide is added while stirring, the pH is adjusted to 12, and centrifugal separation is used to obtain a precipitate; S3, the above product is repeatedly washed with anhydrous ethanol and distilled water, then is placed in an 85°C oven for drying for 24 h, then is placed in a tube furnace and calcined at 500°C in an air atmosphere for 2 h to remove impurities, and then is placed in a tube furnace and heat-treated at 600°C in a hydrogen atmosphere for 3 h, to obtain yttrium oxide nanoparticles coated with elemental tungsten; S4, the prepared nanoparticles are dispersed in 2 kg of Fe-Cr-Al stainless steel powder for additive manufacturing in anhydrous ethanol, mechanical stirring + ultrasonic dispersion is carried out until there is no obvious color stratification, the mechanical stirring time is 2 h, the ultrasonic power is 100 W, then drying is carried out to obtain a mixed powder, the metal powder for additive manufacturing maintains good sphericity, and the prepared nano-oxides are uniformly dispersed on the surface.

[0041] S5, the mixed powder is used for additive manufacturing to obtain an ODS FeCrAl stainless steel with dispersed nano-oxides, the tensile strength is 767 MPa, the oxide distribution is dispersed and uniform, and the average size is 19.8 nm.

[0042] Comparative Example 1 A preparation method of an ODS FeCrAl stainless steel with dispersed nano-oxides, comprising the following steps: S1, 2 g of 50 nm Y2O3 and 1 g of polyvinylpyrrolidone are added to 200 mL of an ethanol solution, and ultrasonic + mechanical stirring is used to ensure that the nanoparticles are fully dispersed; S2, while stirring, add sodium hydroxide, adjust pH to 12, and obtain precipitate by centrifugal separation; S3, the above product is repeatedly washed with anhydrous ethanol and distilled water, then dried in an oven at 85°C for 20h, then calcined at 600°C in air for 1h to remove impurities, and then heat treated at 700°C in hydrogen for 2h to obtain pure yttrium oxide nanoparticles; S4, disperse the yttrium oxide nanoparticles and 2kg Fe-Cr-Al stainless steel powder for additive manufacturing in anhydrous ethanol, and perform mechanical stirring + ultrasonic dispersion until there is no obvious color stratification, the mechanical stirring time is 3h, and the ultrasonic power is 200W, then perform drying to obtain a mixed powder S5, use the mixed powder for additive manufacturing to obtain ODS FeCrAl stainless steel with dispersedly distributed nano-oxides, the tensile strength is 696 MPa, and the average size of the oxides is 28.2 nm.

[0043] Comparative Example 2 A method for preparing an ODS FeCrAl stainless steel, comprising the following steps: S1, add 2g of 50nm Y2O3 to 2kg of Fe-Cr-Al stainless steel powder for additive manufacturing, mix using a ball mill, the ball mill speed is 300r / min, the ball-to-material ratio is 5:1, and the running time is 12h.

[0044] S5, use the mixed powder for additive manufacturing to obtain ODS FeCrAl stainless steel with dispersedly distributed nano-oxides, the tensile strength is 657 MPa, and the average size of the oxides is 36.12 nm.

[0045] Among them, according to the final preparation of ODS alloy performance and nano-oxide size of Example 1, Example 2, Example 3, Comparative Example 1 and Comparative Example 2, the tensile strength of the FeCrAl ODS stainless steel prepared in Example 1 reaches 773 MPa, and the average size of the nano-oxides is 18.3 nm; the tensile strength of the FeCrAl ODS stainless steel prepared in Example 2 reaches 767 MPa, and the average size of the nano-oxides is 19.8 nm; the tensile strength of the FeCrAl ODS stainless steel prepared in Example 3 reaches 760 MPa, and the average size of the nano-oxides is 19.5 nm; the tensile strength of the FeCrAl ODS stainless steel prepared in Comparative Example 1 reaches 704 Mpa, and the average size of the nano-oxides is 28.2 nm; the tensile strength of the FeCrAl ODS stainless steel prepared in Comparative Example 2 reaches 657 Mpa, and the average size of the nano-oxides is 36.12 nm; the overall level of the examples is higher than that of the comparative examples, and the effect of Example 1 is the best.

[0046] The above merely describes the preferred embodiments of the present application, and is not intended to limit the patent scope of the present application. Any equivalent structural variations or direct / indirect applications in other related technical fields based on the content of the present application description are included in the patent protection scope of the present application.

Claims

1. A method of producing an ODS alloy having a dispersion of nanosized oxides, characterized in that, The method comprises the following steps: S1, adding nanometer rare earth oxide and dispersant into liquid to disperse sufficiently, to obtain a mixture of nanometer particles dispersed sufficiently; S2, adding soluble metal salt into the mixture to dissolve the metal salt, and adding pH regulator to adjust pH under stirring, to make the metal salt hydrolyze and precipitate sufficiently to coat the surface of nanometer rare earth oxide; S3, extracting the precipitate to wash and dry, and calcining the dried powder in air atmosphere, and reducing in reducing atmosphere, to obtain nanometer rare earth oxide particles coated with metal element; S4, mechanically stirring and ultrasonic dispersing the nanometer rare earth oxide particles coated with metal element and metal powder for additive manufacturing in liquid until no obvious color stratification, and then drying to obtain mixed powder, and using the mixed powder to perform additive manufacturing, to obtain ODS alloy with dispersed nanometer oxide.

2. The method of claim 1, wherein the ODS alloy with a dispersed distribution of nanooxide is produced by a process comprising: In the step S1, the rare earth oxide is at least one of cerium oxide, yttrium oxide, lanthanum oxide and erbium oxide.

3. The method of claim 1, wherein the ODS alloy with a dispersed distribution of nanooxide is produced by a process comprising: In the step S1, the dispersant is polyvinylpyrrolidone or sodium dodecyl sulfate; the liquid is ultrapure water, deionized water or ethanol solution; and the mixture is colloid or suspension.

4. The method of claim 1, wherein the ODS alloy with a dispersed distribution of nanooxide is produced by a process comprising: In the step S2, the metal salt is iron nitrate, ethyl alcohol iron, ammonium metatungstate or ammonium paratungstate; the pH regulator is ammonia or sodium hydroxide, and the adjusted pH is 8-12.

5. The method of claim 1, wherein the ODS alloy with a dispersed distribution of nanooxide is produced by a process comprising: In the step S2, the molar ratio of metal ions introduced by the metal salt to nanometer rare earth oxide is (1-5):

1.

6. The method of making an ODS alloy with a dispersed distribution of nanooxides of claim 1, wherein, In the step S3, anhydrous ethanol and distilled water are used for washing, the drying temperature is 60-90℃, and the drying time is 6-12h.

7. The method of claim 1, wherein the ODS alloy with a dispersed distribution of nanooxide is produced by a process comprising: In the step S3, the calcination temperature is 400-600℃, the calcination time is 0.5-2h; the reducing atmosphere is hydrogen, the reducing temperature is 600-900℃, and the reducing time is 1-3h.

8. The method of claim 1, wherein the ODS alloy with a dispersed distribution of nanooxide is produced by a process comprising: In the step S4, the liquid is deionized water or ethanol solution; the mechanical stirring time is 2-4h, and the ultrasonic power is 100-400W.

9. An ODS alloy having a dispersion of nanosize oxides, characterized in that, The ODS alloy with dispersed nanometer oxide is prepared by the method of any one of claims 1-8.

10. The ODS alloy with a diffusely distributed nano-oxides of claim 9, wherein, The dispersed nanometer rare earth oxide is nanometer rare earth oxide coated with metal element with core-shell structure, and the size is below 20nm.

Citation Information

Cited By

  • Metal wire solid-state additive manufacturing method based on alternating contact resistance heat

    CN122099526A

  • Astronautical aluminum-lithium alloy brace 3D printing light weight method

    CN122400593B